Pengendalian Kelembaban Tanah dan pH pada Tanaman Kecambah: Sistem Irigasi Otomatis untuk Budidaya Kecambah Kaya Nutrisi Menggunakan Arduino Uno - Adi Winarno; akhmad solikin; Risyaf, Muhammad; Adi, Winarno (Universitas PGRI Adi Buana Surabaya, 2024)
Sprout cultivation is one of the practical and economical methods to obtain a type of food rich in nutrients. However, the success of sprout cultivation requires proper control of soil moisture and water pH in the cultivation environment. Watering begins when the moisture of the mung bean plant reaches the specified parameters with a soil moisture of 67 and a pH value of + 9. This tool aims to make manual work easier to automate, a benefit in watering sprout plants. This tool uses a water ph sensor and a soil moisture sensor or soil moisture sensor that functions as a soil moisture detector that will send commands to the Arduino uno to turn on the relay so that the water pump can automatically water according to the needs of the soil. The creation of this final project is carried out by designing, making and implementing system components which include Arduino uno as a controller, relay to turn on the water pump and turn off the water pump, LCD (linquit Crystal Display) to display the soil moisture value and water ph value. The results of the research value prove that the tools to be made can function properly and can be developed as expected.